PENGARUH PENGGUNAAN MIND MAP TERHADAP KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI DOMINASI OTAK KIRI DAN OTAK KANAN - Maulidyah, Pipid Nirmala; Yohanes, Rudi Santoso (Educatio Vitae, 2015)
This research aims to determine: (1) whether the ability to solve mathematical problems between groups of students who are taught by the expository method + mind map is better than the group of students who are taught by the expository method. (2) whether the ability to solve mathematical problems between groups of students who are taught by the expository method + mind map is better than the group of students who are taught by the expository method to for groups of students who are left brain dominant. (3) whether the ability to solve mathematical problems between groups of students who are taught by the expository method + mind map is better than the group of students who are taught by the expository method to for groups of students who are right brain dominant. This research is a quasi experimental quantitative research. This research was conducted for the eight grade in SMPN 1 Madiun and samples of class VIII A as a class experiment using expository + mind map and eight grade as class B control with expository. Samples were determined by the ability to solve mathematical problems and a questionnaire brain dominance. The first hypothesis is concluded that the ability to solve mathematical problems with expository + mind map is not better than the ability to solve mathematical problems with expository. The second and third hypotheses provide the same conclusion with the first hypothesis.